2016
DOI: 10.1186/s12931-016-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

The cellular kinetics of lung alveolar epithelial cells and its relationship with lung tissue repair after acute lung injury

Abstract: BackgroundOrgan regeneration in mammals is hypothesized to require a functional pool of stem or progenitor cells, but the role of these cells in lung regeneration is unknown.MethodsBased on the fact that postnatal regeneration of alveolar tissue has been attributed to alveolar epithelial cells, we established a hemorrhagic shock and Lipopolysaccharide (LPS) lung injury model. Using this model, we analyzed the cellular kinetics of lung alveolar epithelial cells.ResultsThe results showed that alveolar epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…On the seventh day after ALI, the number of YAP1+ cells began to decline (Figure B). The expression time irregularity of YAP in lung tissue after ALI was consistent with that of AEC2s proliferation (Zeng et al, ); therefore, we supposed that AEC2s could be the main cells expressing YAP1 after ALI.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…On the seventh day after ALI, the number of YAP1+ cells began to decline (Figure B). The expression time irregularity of YAP in lung tissue after ALI was consistent with that of AEC2s proliferation (Zeng et al, ); therefore, we supposed that AEC2s could be the main cells expressing YAP1 after ALI.…”
Section: Resultssupporting
confidence: 84%
“…The expression began to decline on the seventh day after injury ( Figure 1B). The changes in Hippo-YAP expression were consistent with the regular pattern of AEC2 proliferation after ALI (Zeng et al, 2016). The expression of Mer in Hippo pathway increased on the first and fifth day post ALI, while the expression of Ajuba in Hippo pathway increased on the third day post ALI.…”
Section: Expression Of the Hippo-yap Pathway At Various Time Points Asupporting
confidence: 79%
See 2 more Smart Citations
“…In this study, both in vivo and in vitro data showed that PSN inhibited pro-inflammatory cytokine expression and protected against LPS-induced ALI and inflammatory responses. During the early stage of lung injury, inflammatory cells, especially neutrophils and macrophages, are recruited into lungs and contribute to LPS-induced inflammatory responses [46][47][48] , including the production of nitric oxide (NO) and inflammatory cytokines (eg, TNF-α, IL-1β, and IL-6) [2,3] . The expression of iNOS and NO are hallmarks of classically activated macrophages.…”
Section: Discussionmentioning
confidence: 99%